Model for Network Security Service Provider Selection with probabilistic uncertain linguistic TODIM method based on prospect theory - Zhao, Mengwei; Gao, Hui; Wei, Guiwu; Wei, Cun; Guo, Yanfeng (Technological and Economic Development of Economy, 2022)
Choosing the optimal network security service provider (NSSP) is a very important part of enterprise management decision. And the choice of NSSP is a typical multiple attribute group decision making (MAGDM) issue. In order to provide a better decision method for MAGDM problems, this paper integrates the TODIM method and the probabilistic uncertainty linguistic term set (PULTS), so as to propose the probabilistic uncertain linguistic TODIM model based on the prospect theory (PT-PUL-TODIM). The model combines the advantages of the prospect theory and TODIM method. In the end, a case study concerning NSSP selection problem is given to demonstrate the merits of the developed methods.First published online 31 March 2022